Sistem Fonem Isolek Kuntu Kabupaten Kampar - Atri Kehana Masni (Balai Bahasa Sumatera Utara, 2021)
This synchronic study describes the phoneme system of the Kuntu isolect, one of the isolects used in Kampar Regency, Riau Province. The data is the informant's speech using the Kuntu isolect related to the prepared vocabulary. Data was collected by recording and interviewing selected informants, using the listening and speaking method, and analyzed using the equivalent method and the basic premise of Pike (1966). Based on the results of the analysis, IKKK has 42 sounds, namely vocoid, contoid, and diphthong sounds. The IKKK phoneme system has 33 phonemes consisting of five vowel phonemes, eighteen consonant phonemes, and ten diphthong phonemes. Kuntu isolect syllables consist of eight patterns, namely V, VK, KV, KD, KVK, KKV, KDK, and KKVK. The diversity of Kuntu isolect diphthong phonemes found in this study is not much different from previous studies. This proves that the Kuntu isolect of Kampar Regency is a Minangkabau dialect even though Kuntu Village is administratively located in the Riau Province. In addition, the customary system used by the people of Kuntu Village (matrilineal) is another proof that Kuntu Village, Kampar Regency has a relationship with Minangkabau